2014
DOI: 10.1002/prp2.44
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolic pathways and enzyme systems involved in the in vitro human hepatic metabolism of dronedarone, a potent new oral antiarrhythmic drug

Abstract: The in vitro metabolism of dronedarone and its major metabolites has been studied in human liver microsomes and cryopreserved hepatocytes in primary culture through the use of specific or total cytochrome P450 (CYP) and monoamine oxidase (MAO) inhibitors. The identification of the main metabolites and enzymes participating in their metabolism was also elucidated by using rhCYP, rhMAO, flavin monooxygenases (rhFMO) and UDP-glucuronosyltransferases (rhUGT) and liquid chromatography/tandem mass spectrometry (LC/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
5
21
0
Order By: Relevance
“…Our in vitro assay using rCYP450 confirmed that dronedarone is extensively metabolized by CYP3A4 and CYP3A5, in agreement with a previous report (Klieber et al, 2014). Additionally, we found that although CYP2D6 and CYP2C19 contribute to the metabolism of dronedarone, CYP2C8, CYP2C9, CYP1A2, and CYP2E1 do not metabolize dronedarone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our in vitro assay using rCYP450 confirmed that dronedarone is extensively metabolized by CYP3A4 and CYP3A5, in agreement with a previous report (Klieber et al, 2014). Additionally, we found that although CYP2D6 and CYP2C19 contribute to the metabolism of dronedarone, CYP2C8, CYP2C9, CYP1A2, and CYP2E1 do not metabolize dronedarone.…”
Section: Discussionsupporting
confidence: 92%
“…Our in vitro observation that NDBD is the main metabolite of dronedarone is consistent with clinical data that the plasma systemic exposure of NDBD is approximately half that of its parent drug following oral administration (USFDA, 2008). Notably, NDBD is pharmacologically active in vivo (USFDA, 2008) and is further oxidized by CYP3A4 (Klieber et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both drugs are metabolized by CYP3A4 (37, 4044) as shown in Figure 1, and both are involved in drug-drug interactions (3639, 41). Importantly, the highly lever-aged effects of Multaq interactions with multiple cardiac ion channels(45) make interaction with other commonly prescribed medications, such as Lipitor, extremely relevant.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dronedarone can be detected within 24 h incubation in metabolically competent human primary hepatocytes (Klieber et al 2014). Therefore, in the current study, the cytotoxicity of dronedarone was initially investigated at various concentrations below 10 μM for a longer time (24 h).…”
Section: Resultsmentioning
confidence: 99%